Sciatic Nerve Intrafascicular Injection Induces Neuropathy by Activating the Matrix Modulators MMP-9 and TIMP-1 - Tseng, Kuang-Yi; Wang, Hung-Chen; Cheng, Kai-Feng; Wang, Yi-Hsuan; Chang, Lin-Li; Cheng, Kuang-I (Frontiers in Pharmacology, 2022)
Background: Peripheral nerve block (PNB) under echo guidance may not prevent intrafascicular anesthetic injection-induced nerve injury. This study investigated whether unintended needle piercing alone, or the intrafascicular nerve injectant could induce neuropathic pain. Methods: Ninety-six adult male Sprague-Dawley rats were divided into four groups: (1) group S, only the left sciatic nerve was exposed; (2) group InF-P, the left sciatic nerve was exposed and pierced with a 30 G needle; (3) group InF-S, left sciatic nerve was exposed and injected with saline (0.9% NaCl 30 µl); (4) group InF-R, left sciatic nerve was exposed and injected with 0.5% (5 mg/mL, 30 µL) ropivacaine. The hindpaw responses to thermal and mechanical stimuli, barrier permeability, tight junction protein expression, and macrophage infiltration were assessed. Pro-inflammatory cytokine expression and TIMP-1 and MMP-9 activation at the injection site and the swollen, and distal regions of the sciatic nerve were measured by cytokine array, western blotting, and immunofluorescence of POh14 and POD3. Results: The intrafascicular saline and ropivacaine injections into the sciatic nerve, but not needle piercing alone, significantly induced mechanical allodynia that lasted for seven days. In addition, the prior groups increased vascular permeability and macrophage infiltration, especially in the swollen region of the sciatic nerve. Thermal hypersensitivity was induced and lasted for only three days after intrafascicular saline injection. Obvious upregulation of TIMP-1 and MMP-9 on POh14 occurred regardless of intrafasicular injection or needle piercing. Compared to the needle piercing group, the ratio of MMP-9/TIMP-1 was significantly higher in the intrafascicular injection groups at the injected and swollen sites of the sciatic nerve. No gross changes in the tight junction proteins (claudin-5 and ZO-1) but neurovascular barrier edematous change in swollen section of intrafascicular saline. Cytokine array testings showed no obvious changes in pro-inflammatory cytokine expressions between treatment groups. Conclusion: Intrafascicular nerve injection is a distinct mechanism that induces neuropathy by dramatically increasing MMP-9 enzymatic activity and activating TIMP-1 within just a few hours, which contributes to extracellular matrix degradation, increases vascular permeability, and induces neuropathic pain.